KONSEP "TALAM" DALAM PROGRAM ACARA TELEVISI MENGUPAS ACARA TELEVISI DARI SISI LOGIKA DAN MORALITAS - Sudiono, Bambang (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
In recent years television studies have been characterize by a developing concern with research into audience. Discussion about the television audience, have proliferated. This emerging interest did not derive its energy from speculating, solely on the basis television programmes themselves, about how audiences were support to react. And within the messiness of everyday life, the audience are recognize as possessing a complex membership of different gander, class and generational.